(untitled) (Journal of Hama University, 2022)
SThe current study aims to verify the effectiveness of the programme of sports activities at reducing the physical aggressive behavior of 12-year-old pupils at the Izz al-Din al-Qassam School in Jabalah city of the Directorate of Education in Latakia governorate. The study was Conducted on a group of pupils showing some aggressive behavior, the pilot group included 12 pupils with aggressive behavior. The results showed the effectiveness of the sports-based programme and its positive impact at reducing the physical aggressive behavior of the pupils’ target sample.